Analisis Strategi Pengembangan Destinasi Wisata Berdasarkan Komponen 6a Di Tugu Khatulistiwa, Pontianak, Kalimantan Barat - Kurniawan, Johannes; Laurent , Chelsea (Universitas Muhammadiyah Jember, 2023)
Tugu Khatulistiwa is a monument that was erected during the reign of the Dutch East Indies as a marker for the 0o point of the equator. Tugu Khatulistiwa is one of the most famous landmarks in Pontianak City. Tugu Khatulistiwa is currently managed by the Pontianak City Sports and Tourism Youth Service (Disporapar) through the City Government (Pemkot). The Pontianak City Disporapar has the responsibility to prepare and formulate technical policies in the field of attractiveness and management of facilities and infrastructure tourism destinations. The reason and purpose of this study is to analyze the 6A components, namely Attraction, Amenities, Ancillary, Activity, Accessibilities, Available Packages. The type of research used is qualitative research with data collection methods of observation, interviews, and documentation. The analytical method used is triangulation and SWOT analysis (Strength, Weakness, Opportunity, Threats) and SWOT Matrix. The results of the study show that there are 6A components at Tugu Khatulistiwa which are still not optimal because there are still big problems related to the amenities component, but for other attractions, ancillary, activities, accessibilities, & available packages can be increased again to increase the level of visits, needs, and tourist comfort.